Clonidine for preventing emergence agitation in infants (PREVENT AGITATION II): Protocol and statistical analysis plan. Issue 5 (27th February 2023) - Garioud, Anne Louise de Barros; Nielsen, Bettina Nygaard; Falcon, Lars; Mondrup, Frederik; Afshari, Arash
Abstract: Background: Emergence agitation is a common clinical condition in children. Symptoms pertaining to the spectrum of early postoperative negative behavior typically occur upon emergence from anesthesia. Clonidine is an effective adjunctive agent for the prevention of emergence agitation in children, but evidence in the smallest age groups is sparse We aim to investigate the efficacy and safety of an intraoperative bolus of intravenous clonidine for preventing emergence agitation in children 3–12 months of age. Methods: This is a randomized, placebo‐controlled, double‐blind trial. We will enroll 320 patients aged 3–12 months who have been scheduled for general anesthesia maintained with sevoflurane and opioid. The randomization is parallel and stratified by age group, sex, and site. The investigational medicinal product will be administered intravenously 20 min before the anticipated end of the surgical procedure. The intervention is clonidine 3 μg/kg and placebo is isotonic saline in a corresponding volume. Results: The primary outcome is the incidence of emergence agitation as assessed on the Watcha scale, that is, any Watcha score >2 during participants' stay in the postanesthetic care unit. Secondary outcomes are the proportion of participants with postoperative pain, with postoperative nausea and vomiting, and a composite safety outcome. Statistical analysis will be conducted according to the Statistical Analysis Plan with the intention‐to‐treat population for our primary analyses. Conclusion: The PREVENT AGITATION II trial will contribute valuable knowledge on efficacy for the prevention of emergence agitation and safety in infants.